Geoheritage, geoconservation, and geotourism promotion in Costa Rica - Pérez Umaña, Dennis (2024)
Tourism became one of the most important sectors of the economy in Costa Rica since the end of the 1980s. It is from the massive arrival of international tourists attracted by the ecotourism offer based on a robust national system of conservation areas as well as from a rapid adaptation of both public and private sectors that investments in projects to improve the conditions of access, dissemination, and diversification of tourist attractions throughout the country have been increasing steadily. This work shows the main geoheritage and geodiversity characteristics of Costa Rica and focus on an evaluation of the 28 national parks (NP) of the total protected areas of the National System of Conservation Areas (SINAC) for a landscape and aesthetic, cultural, didactic, scientific, and tourism evaluation as potential geoparks. The evaluation determined that 13 of the NPs obtained a high rating, 11 were catalogued as medium, whilst four obtained a low rating. This initiative is an original and novel contribution for Costa Rica since it determines a baseline in the study of geosites and geoparks in the country. In addition, it shows the weaknesses and strengths of each national park in its objective to attract more visitors in the future.